Analysis of Abnormal Return before and after the Announcement of Covid – 19 in Companies Engaged in the Hotel Sector - Joshua Perkasa Naibaho; Martua E. Tambunan; Ketut Silvanita (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
The rate of return on shares that benefit investors will have an impact on the level of investor interest in investing in companies that issue shares. However, the presence of the Covid-19 Virus has almost destroyed the Indonesian economy and even the world. Many businesses have to lose and result in employee layoffs being unavoidable. Therefore, many are interested in playing stocks in order to benefit from the remaining savings. This study aims to determine whether there are differences in abnormal returns before, and after the announcement of the first COVID-19. The period taken is January 02, 2020 to March 9, 2020 or 5 days before and 5 days after the announcement of the pandemic in Indonesia. By using the abnormal return calculation method with a single index model. These results are expected to help investors in choosing the right stocks to become active investors and dare to take high risks by actively buying and selling shares.